PENTINGNYA PEMAHAMAN AGAMA HINDU DENGAN PUSTAKA SUCI, NALAR, LOGIKA VERSUS MULA KETO: (Sebuah Analisis Teori Kritis) - I Komang Sudharka Utama (Pangkaja: Jurnal Agama Hindu, 2023)
Religious life, especially Hinduism in Bali, is very strong and strong in terms of rituals or ceremonies, but weak in terms of tattwa (janana) such as theology or philosophy. The reason is his adherence to the adage 'nak mula keto' (that's how it is). So that people just carry out the ritual obligations without the need to ask anything else question its basis for truth. Consequently, most Hindus are relatively "awidya" (lay knowledge) in terms of understanding tattwa (philosophy), but discipline in terms of perform rituals (ceremonies). Therefore the understanding of Hinduism based on the Sacred Library, Reason and Logic is very important and useful to be used as a foundation in our understanding of religious life. A strong understanding of sacred libraries based on reason and logic will make Hindus become adherents who have strong sradha/faith, are intellectual, modernist, theological, philosophical and scientific. Thus, the adherents will always have an open mind and thirst for knowledge, especially the sacred knowledge of Hinduism. The mula keto tradition that makes people lazy to study sacred literature should be criticized and improved so that people's understanding of Hinduism becomes more in line with tattwa or janana